Usage Effectiveness of Video and Mama Card In Biology Learning of Human Reproductive System - Roihana, Rizky Zulfa; Pukan, Krispinus Kedati; Irsadi, Andin (Journal of Biology Education, 2018)
Student learning outcomes of human reproductive system material under passing grade become an obstacle for students to achieve the learning objectives. Some students are not enthusiastic about human reproductive system material because it is considered difficult. Students still do not understand related to the structure and function of reproductive organ systems, abnormalities and hormones. Based on the problems above then it takes a learning to attract attention or enthusiasm of students. Media is one of the important factors of teaching and learning process. Use of media aims to facilitate teachers in convey learning so students become more easily understand the material. The purpose of this research is to analyze the usage effectiveness of video and mama card in Biology lesson of human reproductive system material. This research used True Experimental Design with Pretest-Posttest Control Group Design. The analysis of data includes quantitative data to student activities and learning outcomes, then descriptive analysis to teacherâs opinion and studentsâ opinion. The result of this research showed that student activities and student learning outcomes in the experimental class is higher than the control class. Teacher and students gave positive reviews to the learning process. Based on the result of research, it was concluded that use of video and mama card was effective in increasing student activities and student learning outcomes in human reproductive system material.